CREBRF promotes the proliferation of human gastric cancer cells via the AKT signaling pathway - Han, Jiming; Zhang, Lu; Zhang, Jing; Jiang, Qiuyu; Tong, Dongdong; Wang, Xiaofei; Gao, Xing; Zhao, Lingyu; Huang, Chen (Cellular and Molecular Biology, 2018)
Gastric cancer (GC) is one of the most common malignant cancer around the world, however the mechanisms is still unclear. In the present study, we investigated the function of CREB3 regulatory factor (CREBRF) in human GC and explored its relevant molecular mechanism. We found that CREBRF was highly expressed in primary GC tissues and the expression level was associated with the clinicopathologic characteristics of GC. CREBRF silencing inhibited GC cell proliferation and induced G1/G0 to S phase cell cycle arrest through regulating Cyclin A, Cyclin D1 and CDK2 expressions. Furthermore, the results showed that knockdown of CREBRF suppressed the activation of AKT signaling pathway. We further discovered that activating of AKT rescued the effect of CREBRF silencing on cell growth and drove cell re-enter into the S phase of the cell cycle with SC79 (a AKT activator). Taken together, our study demonstrated that CREBRF might promote GC cell proliferation and induce G1-S phase transition through activating AKT signaling pathway. These findings suggest that CREBRF acts as a novel oncogene and may be a potential therapeutic target in therapy of GC.